A generalization of multiplier rules for infinite-dimensional optimization problems. (3rd August 2021) - Yilmaz, Hasan
Abstract : We provide a generalization of multiplier rules for infinite-dimensional optimization problems with a finite number of inequality constraints and with a finite number of inequality and equality constraints. Our assumptions on the differentiability of the functions are weaker than those of existing results.